The Australian Recommended Food Score did not predict weight gain in middle‐aged Australian women during six years of follow‐up. (30th July 2013) - Aljadani, Haya M.A.; Sibbritt, David; Patterson, Amanda; Collins, Clare
Abstract Objective : To evaluate the relationship between diet quality score, as measured by the Australian Recommended Food Score (ARFS) and six‐year weight gain in middle‐aged Australian women. Methods : Participants were a sub‐sample of women from the Australian Longitudinal Study on Women's Health (ALSWH) who were followed up from 2001 to 2007 (n= 7, 155, aged 48 to 56 years). The ARFS was derived from responses to a sub‐set of questions from a food frequency questionnaire, with possible scores ranging from 0 to 74 (maximum). Absolute weight gain was calculated from the difference in self‐reported weight between 2001 and 2007. Linear regression was used to test the relationship between diet score and weight change. Results : On average, women gained weight during follow‐up (1.6 ± 6.2 kg) and had a mean baseline ARFS of 32.6 (SD 8.7) which was not optimal. There was no association between ARFS and weight change during follow‐up (β= 0.016; p=0.08) in the fully adjusted model that included total energy intake, education, area of residence, baseline weight, physical activity, smoking and menopause status. Conclusions : Weight gain and low ARFS were common. However, diet quality as measured by the ARFS did not predict six‐year weight gain. Implications : This lack of association may be due to limitations related to AFRS, or may be a false negative finding. Further research is warranted to evaluate the impact of promoting optimal diet quality on weight gain prospectively.